Correlations between nailfold microangiopathy severity, finger dermal thickness and fingertip blood perfusion in systemic sclerosis patients. Issue 1 (3rd May 2013) - Sulli, A; Ruaro, B; Alessandri, E; Pizzorni, C; Cimmino, M A; Zampogna, G; Gallo, M; Cutolo, M
Abstract : Objective: The aim of this study was to identify possible correlations between nailfold microangiopathy severity, finger dermal thickness (DT) and fingertip blood perfusion (FBP) in systemic sclerosis (SSc) patients. Methods: Fifty-seven SSc patients and 37 healthy subjects were enrolled. All patients were evaluated by nailfold videocapillaroscopy (NVC) to classify and score the severity of microangiopathy. Both modified Rodnan skin score (mRss) and skin high-frequency ultrasound were used to detect finger DT. Laser Doppler flowmetry (LDF) was employed to detect FBP. Results: A positive correlation was found between nailfold microvascular damage severity and both ultrasound-DT (p=0.028) and mRss values (p<0.0001). In particular, both ultrasound-DT and mRss were found progressively higher in patients with 'Early', 'Active' or 'Late' NVC pattern of microangiopathy. A negative correlation was observed between nailfold microvascular damage severity and FBP (p<0.0001), showing the lowest FBP of the patients with more advanced NVC patterns. A negative correlation was observed between FBP, and both ultrasound-DT (p=0.007) and mRss values (p=0.0002). SSc patients showed a higher ultrasound-DT at the level of the fingers, as well as a lower FBP than healthy subjects (p<0.0001). Conclusions: This study demonstrates a relationship between nailfold microangiopathy severity, DT and FBP in SSc patients.